A Mind of One's Own: Hegel on Becoming Rational - (:unkn) unknown (My University, 2022)
The `Self-Consciousness' chapter of Hegel's Phenomenology of Spirit has been interpreted in a variety of ways. Traditional readings, however, often do not emphasize Hegel's proclamation that the servile consciousness ``acquires a mind of its own'' and becomes ``thinking consciousness'' in the transition from `Self-Consciousness' A to B. Here, I show how to understand the end of part A and its transition to part B. In this transition, Hegel argues that the servant `comes to have a mind of their own' and becomes `thinking consciousness' or `stoic consciousness' in virtue of beginning to become rational. To this end, I argue that Hegel's argument in `Self-Consciousness' A provides realization conditions for rationality: (1) one must fear and submit to conditions of servitude; (2) one must devote one's practical activity to the service of another; and (3) one must come to understand one's practical activity (service) to have a particular form. Humans are always potentially rational, but they must realize this potentiality by fulfilling these conditions. The argument of `Self-Consciousness' A establishes both that these are the conditions and how they come about. Self-consciousness, as a result, becomes capable of judging propositions to be true or actions good.
Keywords: Freedom; Hegel; Kant; Phenomenology of Spirit; Reason; Self-Consciousness